Successful outcomes of dengue fever management in pregnancy - Oo, Ma Saung; San Thitsa, Aung; Anisah, Jalaluddin; Nik Rafiza, Affendi (2019)
Dengue fever is the most common viral infection transmitted worldwide and major public problem in many countries, particularly in the Southeast Asia region. Dengue infection can present four clinical syndromes such as undifferentiated viral fever, classical dengue fever, dengue haemorrhage fever or dengue shock syndrome. Case reports of dengue fever in pregnancy dramatically increased in Malaysia recently and both adults and children are almost equally affected. Most of the report cases are from an urban area and working and schooling groups are mostly affected. Dengue fever in pregnancy has significant effects and consequences on both mothers and unborn babies particularly in preterm delivery with premature babies. When dengue fever is endemic, clinical prediction and a high index of suspicion in case of any febrile pregnant women are important for achieving favourable maternal and fetal outcomes. The early febrile phase of dengue infection consist of undifferentiated fever and thorough appropriate investigations should be conducted for accurate diagnosis for timely intervention and appropriate further management plan including judicious use of fluid therapy as well as supportive care promptly to prevent further serious maternal and fetal complications. This is a case series of dengue fever in three different trimesters during pregnancy with both favourable maternal and fetal outcomes as more cases of dengue infection in pregnancy can be found due to increasing incidence among adults.